Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Help me calculate the Laplace transform of a geometric series. $$ f(t) = \sum_{n=0}^\infty(-1)^nu(t-n) $$

show that $$ \mathcal{L} \{f(t)\} = \frac{1}{s(1+\mathcal{e}^{-s})} $$

Edit: so far I know that

$$ \mathcal{L} \{f(t)\} = \frac{1}{s}\sum_{n=0}^\infty(-1)^ne^{-ns} $$

share|cite|improve this question
I assume $u(t)$ is the Heavise Step function? – Pedro Tamaroff May 8 '12 at 15:16
Hint: What is the Laplace transform of the shift $u_x(\cdot)\mapsto u(\cdot-x)$? (Use a change of variable). – AD. May 8 '12 at 15:22
I added some extra information as to where I get stuck – ababzy May 8 '12 at 15:38
Write the series as ${1\over s} \sum\limits_{n=0}^\infty \bigl(-e^{-s}\bigr)^n$ and apply the formula giving the sum of a convergent Geometric series. (I think the proposed answer is off...) – David Mitra May 8 '12 at 15:38
For $\sum\limits_{n=0}^\infty (-e^{-s})^n$, the ratio is $r=-e^{-s}$, so the sum is ${1\over 1-r}={1\over 1-(-e^{-s})}={1\over 1+e^{-s}}$; or, am I off? – David Mitra May 8 '12 at 15:52
up vote 4 down vote accepted

Here is a simpler approach.

Note that for $t>0$, we have $f(t)+f(t-1) = 1$. The Laplace transform of a time-shifted function (in this case $f(t-1) = f(t-1) u(t-1)$) is $s \mapsto e^{-s} \hat{f}$, where $\hat{f}$ is the Laplace transform of $f$. Furthermore, the Laplace transform of $1$ is just $s \mapsto \frac{1}{s}$. Hence we have $$\hat{f}(s)+ e^{-s} \hat{f}(s) = \frac{1}{s},$$ from which it follows that

$$\hat{f}(s) = \frac{1}{s(1+e^{-s})}.$$ (Your formula above is incorrect.)

share|cite|improve this answer
That is certainly a clever solution! – Pedro Tamaroff May 8 '12 at 17:50

Try to think what your sum looks like. You will see it is a periodic function, with period $2$, that we can define as.

$$f(t) = 1 ; 0<t<1$$

$$f(t) = 0 ; 1<t<2$$

In general if a function has period $P$, it's LP is given by

$$\mathcal L \{ f(t) \} =\frac{1}{1-e^{-sP}}\int_0^P e^{-st}f(t)dt$$

under appropriate conditions (i.e. the LP should exist)

It this case $f(t)$ is periodically constant, so the LP exists, and

$$\mathcal L \{ f(t) \} =\frac{1}{1-e^{-2s}}\int_0^2 e^{-st}f(t)dt$$

$$\mathcal L \{ f(t) \} =\frac{1}{1-e^{-2s}}\int_0^1e^{-st}dt$$

$$\mathcal L \{ f(t) \} =\frac{1}{1-e^{-2s}}\frac{1-e^{-s}}{s}$$

$$\mathcal L \{ f(t) \} =\frac{1}{1+e^{-s}}\frac{1}{s}$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.